A photocaged inhibitor of acid sphingomyelinase. Issue 94 (12th November 2020) - Prause, Kevin; Naseri, Gita; Schumacher, Fabian; Kappe, Christian; Kleuser, Burkhard; Arenz, Christoph
Abstract : An esterase-labile, photocaged inhibitor provides spatiotemporal control over acid sphingomyelinase in living cells. Abstract : Acid sphingomyelinase (ASM) is a potential drug target and involved in rapid lipid signalling events. However, there are no tools available to adequately study such processes. Based on a non cell-permeable PtdIns(3, 5)P2 inhibitor of ASM, we developed a compound with o -nitrobenzyl photocages and butyryl esters to transiently mask hydroxyl groups. This resulted in a potent light-inducible photocaged ASM inhibitor (PCAI ). The first example of a time-resolved inhibition of ASM was shown in intact living cells.